Pengaruh Administrasi Perpajakan, Kualitas Pelayanan Perpajakan, Kesadaran Wajib Pajak, dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak Pajak Bumi dan Bangunan Kecamatan Panekan Kabupaten Magetan - Riyandi Dwi Efendi; Andri Hasmoro Kusumo Broto (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2021)
Taxes are the main source of state revenue that can be used for financing, government spending and development. Where tax revenue is the largest domestic revenue. This type of research is a quantitative research. The population in this study amounted to 88 taxpayers and a sample of 88 respondents. Data collection techniques using questionnaires and documentation. The analysis technique uses multiple linear regression. The results obtained indicate that (1) there is a positive and significant effect of tax administration on the compliance of land and building taxpayers in Panekan District, Magetan Regency; (2) There is a positive and significant effect of the quality of tax services on the compliance of taxpayers on land and building taxes in Panekan District, Magetan Regency; (3) There is a positive and significant impact of taxpayer awareness on the compliance of land and building taxpayers in Panekan District, Magetan Regency; (4) There is a positive and significant effect of tax sanctions on the compliance of taxpayers on land and building tax in Panekan District, Magetan Regency; and (5) There is a positive and significant effect simultaneously on tax administration, quality of tax services, taxpayer awareness and tax sanctions on land and building tax compliance in Panekan District, Magetan Regency.